UCov: a user‐defined coverage criterion for test case intent verification. (27th June 2016) - Assi, Rawad Abou; Masri, Wes; Zaraket, Fadi
Summary: The goal of regression testing is to ensure that the behaviour of existing code, believed correct by previous testing, is not altered by new program changes. This paper argues that the primary focus of regression testing should be on code associated with (1) earlier bug fixes and (2) particular application scenarios considered to be important by the developer or tester. Existing coverage criteria do not enable such focus, for example, 100% branch coverage does not guarantee that a given bug fix is exercised or a given application scenario is tested. Therefore, there is a need for a new and complementary coverage criterion in which the user can define a test requirement characterizing a given behaviour to be covered as opposed to choosing from a pool of pre‐defined and generic program elements. This paper proposes this new methodology and calls it UCov, a user‐defined coverage criterion wherein a test requirement is an execution pattern of program elements, and possibly predicates, that a test case must satisfy. The proposed criterion is not meant to replace existing criteria, but to complement them as it focuses the testing on important code patterns that could go untested otherwise. UCov supports test case intent verification . For example, following a bug fix, the testing team may augment the regression suite with the test case that revealed the bug. However, this test case might become obsolete due to code modifications not related to the bug. But if a test requirement characterizing the bug was defined by the user, UCov would determine that test case intent verification failed. The UCov methodology was implemented for the Java platform, was successfully applied onto 10 real‐life case studies and was shown to have advantages over JUnit . The implementation comprises the following tools: (1) TRSpec : allows the user to easily specify complex test requirements; (2) TRCheck : checks whether user‐defined test requirements were satisfied, that is, supports test case intent verification; and (3) TRMigrate : migrates user‐defined test requirements to subsequent versions of a given program. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Existing coverage criteria, for example, branch coverage, do not guarantee that a given bug fix is exercised or a given scenario is tested. Therefore, there is a need for a coverage criterion in which the user can define a test requirement characterizing a given behavior to be covered as opposed to choosing from a pool of generic program elements. This paper proposes UCov, a user‐defined coverage criterion that focuses the testing on important code patterns that could go untested otherwise.